ChemInform Abstract: Infinite Anionic Chains Formed by Alternating Bidentately Acting [SbS4]3‐ Anions and [Mn(dien)]2+ Complexes in the Compound [Mn(dien)]2[Mn(dien)SbS4]2. Issue 37 (22nd August 2013) - Herzberg, Nicola; Naether, Christian; Bensch, Wolfgang
Abstract [Mn(dien)2][Mn(dien)SbS4]2 (dien: diethylenetriamine) is synthesized under solvothermal conditions using stoichiometric amounts of Mn, Sb, and S in dien (autoclave, 140 °C, 2 d, 5—15% yield).